Antibacterial and antispore activities of Sengkubak [Pycnarrhena cauliflora (Miers.) Diels] leaf extract against Bacillus spp - Suil, S.J.M.; Rinai, K.R.; Rukayadi, Y.; Abas, F.; R., Son (Rynnye Lyan Resources, 2025)
Sengkubak [Pycnarrhena cauliflora (Miers.) Diels], a liana plant used as a spice in Dayak cuisine, has been reported to possess antimicrobial activity. However, the antibacterial and antispore activities of its methanolic and ethanolic leaf extracts against Bacillus species are not well-known. In this study, the antibacterial properties of P. cauliflora leaf extracts were evaluated against four Bacillus strains. The susceptibility test was conducted using the disc diffusion assay, minimum inhibitory concentrations (MIC), and minimum bactericidal concentrations (MBC), according to the Clinical and Laboratory Standard Institute's recommendations. Time-kill curve analysis was performed at different exposure durations and concentrations. The results showed that P. cauliflora leaf extract exhibited antibacterial activity against all Bacillus species tested, with inhibition zones ranging from 8.67±0.58 to 9.33±0.58 mm, MICs ranging from 0.938±0.44 to 1.25±0.00 mg/mL, and MBC values ranging from 3.75±1.77 to 5.00±0.00 mg/mL. Time-kill curve analysis demonstrated that the P. cauliflora leaf extract significantly reduced the growth of Bacillus spp. vegetative cells and the bactericidal endpoint was reached at 4×MIC after 4 hrs of incubations. Furthermore, P. cauliflora leaf extract inactivated Bacillus spp. spores significantly after incubation for 4 hrs at concentrations of 0.5%, 1%, 2.5% and 5%. At a concentration of 5%, the extract inactivated 99% of the spores after 1 hr incubation. These findings suggested that P. cauliflora leaf extract has potential as an antibacterial agent against Bacillus species.